2005
DOI: 10.1542/peds.2004-0341
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depressive Symptoms and Children's Receipt of Health Care in the First 3 Years of Life

Abstract: Maternal depressive symptoms in early infancy contribute to unfavorable patterns of health care seeking for children. Increased provider training for recognizing maternal depressive symptoms in office settings, more effective systems of referral, and development of partnerships between adult and pediatric providers could contribute to enhanced receipt of care among young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
263
7
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 346 publications
(299 citation statements)
references
References 33 publications
22
263
7
4
Order By: Relevance
“…In a sample of children ages 0 to 30 months, Minkovitz et al (2005) examined medical records and maternal reports of depressive symptoms measured by the CES-D (Radloff, 1977). Acute pediatric use including hospitalizations, emergency department visits and preventive care (i.e., "well baby" visits, vaccination appointments) were examined using medical records and parental interviews conducted at 2 to 4 and 30 to 33 months of age.…”
Section: Maternal Negative Affect and Pediatric Health Care Usementioning
confidence: 99%
“…In a sample of children ages 0 to 30 months, Minkovitz et al (2005) examined medical records and maternal reports of depressive symptoms measured by the CES-D (Radloff, 1977). Acute pediatric use including hospitalizations, emergency department visits and preventive care (i.e., "well baby" visits, vaccination appointments) were examined using medical records and parental interviews conducted at 2 to 4 and 30 to 33 months of age.…”
Section: Maternal Negative Affect and Pediatric Health Care Usementioning
confidence: 99%
“…Depressed mothers are less likely to provide a smoke-free home [2] or read to their children daily [1]. They are less likely to provide age-appropriate well-child visits [4]. Children of depressed mothers are more likely to be injured [4].…”
mentioning
confidence: 99%
“…They are less likely to provide age-appropriate well-child visits [4]. Children of depressed mothers are more likely to be injured [4]. One study suggested that depressed fathers have a synergistic negative impact [5].…”
mentioning
confidence: 99%
“…The results from previous studies also indicated that postnatal depression in populations other than earthquake survivors may be significantly related to cessation of breast-feeding [8,34], degradation of mother-infant attachment [29], more concerns about the baby [35], and unfavorable patterns of seeking healthcare services [36]. These outcomes may also be applicable for women with high EPDS scores living in the disaster area.…”
Section: Discussionmentioning
confidence: 92%